2022
DOI: 10.2196/33073
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and Provider-Reported Experiences of a Mobile Novel Digital Therapeutic in People With Opioid Use Disorder (reSET-O): Feasibility and Acceptability Study

Abstract: Background Medications for the treatment of opioid use disorder, such as buprenorphine, are effective and essential for addressing the opioid epidemic. However, high dropout rates from medication remain a challenge. Behavioral treatment with contingency management and cognitive behavioral counseling has shown promise for improving the outcomes of buprenorphine treatment but is complicated to deliver. The delivery of behavioral treatment through technology-based platforms has the potential to make i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Studies [ 27 , 55 ] have shown that the probabilities of hospitalization for HF and all-cause mortality were 50% and 81%, respectively, for patients on DTx for home-based CR compared with patients who did not use the program. Results from several randomized controlled trials of studies [ 32 41 ] showed that patients with DTx interventions had higher levels of health improvement, disease symptom relief, and reduced panic or confusion during disease progression. Thus, DTx improved patients’ quality of life with higher psychological status (mood, health beliefs, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [ 27 , 55 ] have shown that the probabilities of hospitalization for HF and all-cause mortality were 50% and 81%, respectively, for patients on DTx for home-based CR compared with patients who did not use the program. Results from several randomized controlled trials of studies [ 32 41 ] showed that patients with DTx interventions had higher levels of health improvement, disease symptom relief, and reduced panic or confusion during disease progression. Thus, DTx improved patients’ quality of life with higher psychological status (mood, health beliefs, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…DTx has been applied to disease treatment, rehabilitation, prevention, and patient management in various fields, such as cardiovascular, endocrine, orthopedic, ophthalmological, neurological, and psychological. The results of several randomized controlled trials [ 32 41 ] showed that patients receiving DTx-based interventions had a higher level of health improvement and disease symptom relief and had significantly better psychological status and quality of life than control patients. In addition, DTx can enhance doctor-patient communication and play an active role in the management of disease risk factors, reduction of healthcare costs, and implementation of precision medicine [ 15 , 42 – 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies 27,55 have shown that the probabilities of hospitalization for HF and all-cause mortality were 50% and 81%, respectively, for patients on DTx for home-based CR compared with patients who did not use the program. Results from several randomized controlled trials of studies 32,33,34,35,36,37,38,39,40,41 showed that patients with DTx interventions had higher levels of health improvement, disease symptom relief, and reduced panic or confusion during disease progression. Thus, DTx improved patients' quality of life with higher psychological status (mood, health beliefs, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…DTx has been applied to disease treatment, rehabilitation, prevention, and patient management in various elds, such as cardiovascular, endocrine, orthopedic, ophthalmological, neurological, and psychological. The results of several randomized controlled trials 32,33,34,35,36,37,38,39,40,41 showed that patients receiving DTxbased interventions had a higher level of health improvement and disease symptom relief and had signi cantly better psychological status and quality of life than control patients. In addition, DTx can enhance doctor-patient communication and play an active role in the management of disease risk factors, reduction of healthcare costs, and implementation of precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Most lessons include a fluency training session (e.g., quiz), and upon successful completion of fluency training, the patient can earn CM rewards (either virtual or tangible via digital gift cards redeemable at participating companies) by spinning the rewards wheel. 11 Patients are eligible for earning CM rewards for completing up to 4 lessons per week or for negative urine drug screens. Prescribing clinicians access patient data and self‐reports via a “clinician dashboard” on a computer or mobile device.…”
Section: Introductionmentioning
confidence: 99%